Echoes and Antibodies: Legal Veridiction and the Emergence of the Perpetual Hepatitis C Subject. (April 2023) - Seear, Kate; Fraser, Suzanne; Mulcahy, Sean; Kagan, Dion; Lenton, Emily; Farrugia, Adrian; valentine, kylie
New drugs with the potential to cure hepatitis C have emerged. There is great optimism within medicine about the transformative potential of cure, but this overlooks the entrenched discrimination and stigma associated with both hepatitis C and injecting drug use and the role of law in re/producing it. Drawing on interviews with key stakeholders such as policymakers, lawyers, and representatives from peer organisations (N = 30), Latour's (2013) work on legal veridiction, Fraser and Seear's (2011) conceptualisation of hepatitis C as a 'gathering', andMol's (2021) work on being, this paper explores the possibility that legal processes complicate the linear trajectory of progress and transformation cure promises. Our participants' identify various legal processes that allow hepatitis C to echo or linger in people's lives after treatment. These processes are remaking hepatitis C, and making perpetual hepatitis C subjects. We argue that we must grapple with these forces in the era of cure.